Understanding Student Engagement in Hybrid Learning : An Analysis Impact Digital Literacy and Academic Self-Efficacy - Jaya, Fitra; Nurqamarani, Adisthy Shabrina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study analyzes student engagement in hybrid learning by analyzing digital literacy and academic self-efficacy. This study used a quantitative approach with the survey as a data collection method. The population in this study was 370 students, the faculty of teacher training and education at state universities in Jakarta, and private universities in Banten and Lampung. The sampling technique used was proportional random sampling, obtained by 105 respondents. Data was collected through questionnaires, and structural equation modeling (SEM) was used to analyze the relationship between constructs. The results of this study state that Digital literacy and academic self-efficacy play an important role in creating student engagement in hybrid learning. The ability of students to use digital learning resources will support active participation in the learning process. A high academic level of self-efficacy also helps them to be able to have confidence and perseverance during the learning process. Digital literacy and academic self-efficacy will bring students to be actively involved in the digital learning environment and play an essential role in shaping or maintaining student motivation and persistence in learning. Students’ engagement levels can be increased by increasing their ability to use digital technology effectively and increasing their confidence that they can achieve their desired academic goals.